Pengaruh Current Ratio, Debt to Asset Ratio, dan Total Asset Turnover Terhadap Return on Asset Pada PT IndoFarma (INAF) Tbk Periode 2014-2023 - Desmaniar, Salwa Anisya; Herlina, Listri; Nugroho, Ilham Winar (Jurnal Ilmu Sosial, Manajemen, Akuntansi dan Bisnis, 2024)
This study aims to examine the effect of the current ratio (CR), debt-to-asset ratio (DAR), and total asset turnover (TATO) on the return on assets (ROA) of PT IndoFarma (INAF) Tbk for the period 2014-2023. This research uses a quantitative approach with descriptive and verification methods. Secondary data from the company's annual financial statements accessed through the company's official website were analyzed using purposive sampling. The data analysis techniques used are descriptive analysis, regression analysis, correlation analysis, coefficient of determination analysis, and partial and simultaneous hypothesis testing. The results showed that partial hypothesis testing (t-test) showed that CR has a significant effect and DAR hurts ROA, while TATO has no significant impact on ROA. The simultaneous hypothesis testing (F-test) shows that CR, DAR, and TATO together have a substantial effect on the ROA of PT IndoFarma (INAF) Tbk during the 2014-2023 period. These results provide insight into the financial and management performance of PT Indo Farma (INAF) Tbk, which can inform decision-making and strategic planning for companies and similar companies in the industry, empowering them with actionable insights.